2011
DOI: 10.17221/1287-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weaning calves from mother at different ages on their growth and milk yield of mothers

Abstract: ABSTRACT:The aim of this study was to determine the impact of the length of calf sucking milk from its own mother on calf growth at the age of 3 months and milk yield of mothers. We tested a hypothesis that the nursing of calves by their own mothers increases the body weight of calves and decreases the milk production. 50 Holstein primiparous cows and their calves were divided into three groups according to the sucking length of calves: 7 days (A), 14 days (B) and 21 days (C). All calves suckled mother's colos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…Long suckling has been associated with lower milk deliveries which were also found in this study. However, several studies have reported that gained milk over the entire lactation may be unaffected for high-yielding cows nursing their calves (Johnsen et al 2015a;Metz 1987;Kišac et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Long suckling has been associated with lower milk deliveries which were also found in this study. However, several studies have reported that gained milk over the entire lactation may be unaffected for high-yielding cows nursing their calves (Johnsen et al 2015a;Metz 1987;Kišac et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The growth and development of an organism is regulated by both internal (integration of signal pathways) and environmental (mainly supplied from feed) factors (Kišac et al, 2011). There are many reports on the significant relationship between the insulin-like growth factors (IGFs) system and the prenatal growth as well as the growth and differentiation of the mammary gland (Plath-Gabler et al, 2001).…”
mentioning
confidence: 99%
“…However, an increase of price could be justified by labelling the product as goods produced according to a certain animal welfare practice (Grethe, 2017). On the other hand, Kišac et al (2011) examined the impact of the length of a calf suckling milk from its own mother on the calf growth and cow production on a Slovak non-organic dairy farm. The results showed that prolonged nursing positively influenced the growth of calves, but reduced the mothers' milk production.…”
Section: Policy and Economicsmentioning
confidence: 99%